A Novel Colorimetric Food Package Label For Fish Spoilage Based On Polyaniline Film - Bambang Kuswandi; Jayus, Anggi Restyana; Aminah Abdullah; Lee Yook Heng; Musa Ahmad (Elsevier B.V, 2024)
Volume 25, Issue 1